An Analysis of Decisions - Salveson, M. E. (Management Science, 1958)
Most analyses of decision making define decision as choosing from among alternative courses of action. Usually, the criterion of choice is assumed to be some function of probability and utility of the different outcomes associated with each course of action. It is shown here that decision is more realistically concerned with constructive, purposive, or creative aspects of human behavior. In addition to the usual decisions of action, other classes of decision include decisions of understanding, of recognition, and of enterprise. These classes are interdependent and their members interrelated in any realistic situation. Organization planning is shown to be concerned largely with interrelating decisions and with providing criteria for decision. The quality of organization planning affects the quality of decisions, the degree of human satisfaction, and the effectiveness of the organization.